Relatives of the first episode psychosis patients: Relations between assessment of the situation’s difficulty and psychological distress over time - Povilaitienė, I.; Gailienė, D.; Pakalniškienė, V. (Psichologija, 2011)
The aim of the study was to assess relationships between the assessment of the situation’s difficulty and psychological distress over time by the relatives of the first episode psychosis patients.The sample of the study comprised 30 relatives (parents 63%, siblings 26%, and partners 10%) of the first episode psychosis patients. Participants of the study were interviewed during the first 10 days after the patient’s admission to the hospital, and then 3 months and 9 months after the first interview. Criteria of the participation in the study: an adult family member of a first-time hospitalized patient; the patient’s diagnosis – psychotic disorder (F20 or F30 with psychosis, ICD-10); a patient no older than 40. The study proceeded at psychiatric hospitals in Vilnius. Relatives: age M = 42.3, SD = 13.24); gender: men 37%, women 63%. Patients: age M = 24.07, SD = 4.87, gender: men 70%, women 30%. The following variables were investigated: demographics, assessment of the situation’s difficulty (perceived psychological trauma subscale (Lewis, 2005)), psychological distress (Hospital Anxiety and Depression Scale (Zigmond and Snaith, 1983)). Data were analyzed by the repeated Anova and testing by the cross-lagged panel design model.The results showed that the relatives’ assessment of the situation’s difficulty and distress improved significantly during the first three months. The prognostic value of distress and the assessment of the situation’s difficulty at Time 1 were different: assessment of the situation’s difficulty overtime was predicted by assessment at Time 1, but the distress overtime was not predicted by the distress at Time 1. Cross-lagged analysis revealed that distress over-time was predicted by the assessment of the situation’s difficulty at Time 1. The results of this study suggest that professionals working with families should pay more attention to diminishing relatives’ negative assessment of the situation from the beginning, because it predicts significantly the later distress.
Keywords: first episode psychosis; relatives; assessment of the situation’s difficulty; psychological distress